The repeatability of smith's method in measuring anterior chamber depth - Sidek, Nur 'Izzati; Yusof @ Alias, Firdaus (Kulliyyah of Allied Health Sciences, International Islamic University MalaysiaIUM Press, 2021)
Aims: The aim of this study is to assess the intra-observer repeatability and the inter-observer limits of agreement of the Smith’s technique in measuring ACD.